Effects of acute taurine consumption on single bout of muscular endurance resistance exercise performance and recovery in resistance trained young male adults - Akalp Kaan; Vatansever Şerife; Sönmez Gül Tiryaki (Sciendo, 2023)
Study aim: This study investigated the effect of taurine supplementation on exercise performance and recovery from resistance exercise. The study was conducted with a cross-over design in a double-blind manner.